Stachybotrins G and H, Two New Phenylspirodrimane Derivatives from the Fungus Stachybotrys chartarum - Wang, Yi; Chen, Kang; Xing, Qiao; Zhang, Tao; Xu, Yuquan (Planta Medica, 2025)
Two new phenylspirodrimane derivatives, designated as stachybotrins G and H (1 and 2), which feature an N-isobutyl side chain, along with four known analogues (3−6), were isolated from the fungus Stachybotrys chartarum. All the structures were determined through comprehensive spectroscopic analyses, primarily based on HRESIMS and NMR data. The antibacterial activity of all isolated compounds was evaluated. Compound 5 demonstrated antibacterial activity against the Gram-positive bacterium Staphylococcus aureus ATCC 6538, with a minimum inhibitory concentration (MIC) value of 6.25 µg/mL.
Keywords: Stachybotrys chartarum; Stachybotryaceae; phenylspirodrimane derivatives; N-isobutyl group; antibacterial activity